Determining the Factors and Their Relative Effect on Offshored Data Privacy: Client and Vendor Perspectives - Anupam K. Nath (STIE Malangkucecwara, 2017)
Offshoring of services has become an inevitable part of business strategy. While businesses are deploying service offshoring for quite some time now, preserving the privacy of the sensitive information of offshored data remains as one of the major challenges and concerns. In this paper, we identify factors that affect the privacypreservation of the offshored data and the conduct of the offshore vendors and their employees towards clients’ data. We deploy a positivist case study method to examine the proposed relationships. We collected qualitative data through semi-structured interviews with the project managers of client organizations as well as from the project managers of vendor organizations to test the proposed model. The result of our study shows that the code of conduct set by the vendor organizations plays the most effective role in the privacy-preserving behavior of the vendors’ employees.